(untitled) (Journal of Economic Research & Business Administration, 2016)
This article describes the main directions of state regulation of the formation and development of intellectual capital, whose task is to ensure the effectiveness of the formation, use and development of intellectual capital. The international instruments of the state to stimulate and sup port innovation. In particular we have reviewed the direct and indirect methods of state regulation of innovative processes. Direct methods of state regulation of innovation processes has been targeted form and ad ministrative departmental form. To indirect methods of state regulation of innovative processes include tax incentives, the organization of innovation infrastructure, marketing activities, the establishment of legal provisions, deferred taxation, the system of accelerated depreciation of fixed capital, etc. Studied foreign practice of normative–legal base of development of intellectual capital.